The Internalization of Islamic Moral Values as a Strategy to Prevent Negative Digital Behavior among Students at SMAN 1 Mojosari - Muhammad Syafi’i Anam (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has had a broad impact on students' social lives, including the emergence of negative behaviors such as the spread of hate speech, inappropriate content, and cyberbullying. This study aims to examine the importance of internalizing Islamic moral values as a preventive strategy against these negative behaviors among students at SMAN 1 Mojosari. The research approach used qualitative methods, with data collection consisting of interviews, observations, and documentation. The results indicate that strengthening Islamic moral values through Islamic Religious Education (PAI) learning, fostering noble behavior, and involving parents and schools effectively reduce students' negative digital behaviors.